Heterotypic pulmonar anomaly in paralumbal region of a calf - Yılmaz Koç; Zeki Oğurtan; Mehmet Tuzcu; Fahrettin Alkan; M. Kemal Çiftçi (Eurasian Journal of Veterinary Sciences)
In this study, heterotypic pulmonar anomaly in a two-day-old female calf was described. Related clinical, radiological and histopathological results were discussed. The heterotypic pulmonar anomaly developed in the left pa-ralumbar region, resulted in depression on the medulla spinalis, hemivertebra in L4, and scoliosis in L4-5